Espectroscopia Mössbauer aplicada ao estudo da liga aço baixo carbono-Al nitretada - Kapp, Mario Sergio Vinicius (Universidade Federal de São Carlos, 2005)
We presented in this work a study of the influence of the thickness of Al thin film deposited in substratum of low carbon steel. Alloys of steel low carbon and aluminum are used broadly in automobile and aerospace industries. We studied the nitrides formation, starting from a process of pre-heat-treatment of the samples in the nitriding camera followed by plasma nitriding, in the temperatures of 300°C and 400°C. The following techniques: Conversion Electrons Mössbauer Spectroscopy (CEMS), X-ray diffraction (XRD), Scan Eletron Microscopy (SEM) and Vickers microhardness test were used for the characterization of those samples. The Aluminium purity for the films was 99,99%. The steel low carbon substrate was supplied by IPT-SP (Institute of Researches Technological-SP) and after the samples be cut and polished, they received the film of aluminum. Soon after they were pre-heat-treated (section 4.1) and nitreded in the temperatures of 300oC and 400oC for 4 hours in composed atmosphere for 80% of H2 and 20%N2. After the nitriding the samples were characterized by the techniques referred above. For the temperature of 300oC, the X-ray Diffraction results showed the formation of the phases α-Fe, Al and AlN. The Mössbauer spectroscopy showed α- Fe and formation of solid solution of Fe in aluminum. For the temperature of 400oC, we still observed the formation of the phase Fe4Al13, for the two techniques. The Mössbauer Spectroscopy also showed that the increase of the percentage of the phase Fe4Al13 has a possible dependence with the nitriding temperature and with the thickness of the film of aluminum. The images of MEV and the Vickers microhardness tests, just revealed the presence of nitrides of iron in the borders of the samples.
Keywords: Física de superfície; Espectroscopia de Mössbauer; Nitretação a plasma; CIENCIAS EXATAS E DA TERRA::FISICA